Modelling Electricity Generation Based on Coal in Türkiye - MOHAMED, YASIR HASSAN (İstanbul Kültür Üniversitesi, 2024)
This thesis investigates electricity generation modeling in Turkey with a focus on coal-fired power plants. Turkey's rapidly rising economy has led to a huge increase in energy consumption, and coal plays a critical role in the energy mix. The study takes a comprehensive approach to analyze various aspects of coal-based energy production, taking into account technical, economic and environmental factors. The thesis uses modeling methods and simulations to predict future trends in coal-fired electricity generation, taking into account various situations such as changes in energy demand, technological advances, and changing regulatory environments. The findings are intended to provide useful insights for policymakers, industry players and academics interested in the long-term growth of Turkey's energy sector. Finally, this thesis provides a comprehensive overview involving technical, economic and environmental factors, contributing to a better understanding of the complex dynamics surrounding coal-fired electricity generation in Turkey. In the context of Turkey's evolving energy environment, the findings aim to guide decision makers and shape plans for the future of coal-based electricity.
Türkiye'de Kömüre Dayalı Elektrik Üretiminin Modellenmesi
Yüksek lisans tezi.
Keywords: Electricity; Demand Forecasting; Time Series Analysis; Linear Regression